2015
DOI: 10.1186/s12970-015-0069-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C, A and E supplementation decreases the expression of HSPA1A and HSPB1 genes in the leukocytes of young polish figure skaters during a 10-day training camp

Abstract: BackgroundOverexpression of HSPA1A and HSPB1 has been shown to indicate stress and the degradation of damaged proteins. Therefore, the expression of these genes is often evaluated during exercise. Vitamin supplementation in young athletes may affect the expression of these genes, and help to maintain health and improve the effects of training.MethodsFourteen top junior female athletes (age 14–15y ± 0.3 SD, body mass 51 kg ± 5 SD, and BMI of 20.15 ± 0.9 SD, time in professional training 8.5 y ± 0.5 SD) attended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…HSPB1 encodes for a heat-shock protein that can protect against oxidative stress. Diet supplementation with antioxidant vitamins resulted in a significant drop in HSPB1 expression in athletes after an exercise period compared with athletes fed an un-supplemented diet [ 130 ]. Over-expression of HSPB1 has been shown to improve stress resistance (including oxidative stress) [ 130 , 131 , 132 , 133 , 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…HSPB1 encodes for a heat-shock protein that can protect against oxidative stress. Diet supplementation with antioxidant vitamins resulted in a significant drop in HSPB1 expression in athletes after an exercise period compared with athletes fed an un-supplemented diet [ 130 ]. Over-expression of HSPB1 has been shown to improve stress resistance (including oxidative stress) [ 130 , 131 , 132 , 133 , 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the gene expression in peripheral blood leukocytes show a systemic response to effort or training and prove the stress load to the body [20,21,22]. The expression of numerous genes may increase locally in skeletal muscles, but there are differences between local and systemic changes in the mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…In our research the changes in genes expression were evaluated in leukocytes, the cells with high antioxidant capacity [ 36 ]. According to Żychowska et al [ 16 ] and Maltseva et al [ 15 ] changes in genes expression in these cells show a systemic response to exercise. Results confirmed that, before and after the applied training period, gene expression differences between lower and upper body exercises were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in genes associated with inflammation and HSP show the result of alterations in signalling via these pathways. There is considerable evidence demonstrating the influence of various exercise types on inflammation [ 13 , 14 ] and gene expression of heat shock proteins [ 15 , 16 ], thereby mediating the health benefits of episodic and prolonged exercise.…”
Section: Introductionmentioning
confidence: 99%